Social bases for the dialogue on deceased organ donation - O. N. Reznik; A. O. Reznik (Вестник трансплантологии и искусственных органов, 2024)
This article assesses the changes in the coverage of the problem of organ donation in Russia. The boundaries of the dialogue on posthumous organ donation are outlined, taking into account the current organ donation model in Russia. The paper defines the concept of social capital, the sociology of organ donation and their significance for the development of deceased organ donation (DOD). Steps to promote the DOD concept in Russia are proposed.